Process and system for preparing carbon dioxide adsorption catalyst from fly ash and lithium battery black powder

By mixing with black powder with lithium batteries with black powder, combined with the corrosion and adsorption deposition method of gas or gas phase+steam phase, the surface area and pores of the catalyst have been improved. The problem of uniformity realizes the high -efficiency resource utilization of flyy ash and lithium battery black powder and the efficient carbon dioxide adsorption effect of catalysts.

CN119346060APending Publication Date: 2025-01-24ZHONGTAIHAI CARBON (SHANGHAI) ENVIRONMENTAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411641411.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing catalyst production methods, it is difficult to evenly load the active substances on the surface of the substrate, and the resource utilization of fly ash and lithium battery black powder are insufficient, making it difficult to be efficiently utilized.

Method used

By mixing the fly ash particles with the lithium battery black powder, and the lithium hydroxide solution is soaked, it is burned to form a catalyst substrate. Then in the reactor, the surface area and pore degree of flyy ash and lithium battery black powder are improved through the corrosion of gas or gas phase+steam phase.

Benefits of technology

Achieve the effective use of flyy ash and lithium battery black powder, improve the carbon dioxide adsorption ability of the catalyst, avoid the problem of blocking the gap or uneven attachment of the catalyst base material during the preparation process, and the process equipment can be continuously operated. Suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a process and a preparation system for preparing a carbon dioxide adsorption catalyst by using fly ash and lithium battery black powder, and the process comprises the following steps: S1, mixing fly ash particles and lithium battery black powder, drying and calcining by using a lithium hydroxide solution, and then conveying to a reactor; s2, conveying an ethanol solution of fluosilicic acid or hydrofluoric acid and n-hexane to a reactor; s3, removing impurities from the catalyst base material in the reactor; s4, after diesel oil is conveyed to the reactor, the fly ash particles in the reactor are purged, so that the diesel oil is rapidly carbonized and loaded on the surfaces of the fly ash particles; and S5, mixing an n-hexane solution of silica gel with the fly ash particles, adding a silane coupling agent, mixing, and then drying and cooling. The characteristic that lithium, activated carbon and silica gel adsorb carbon dioxide is utilized, and the catalytic adsorbent is treated, so that the voidage and the specific surface area of the adsorbent are deepened; the adsorption capacity of the adsorption catalyst on carbon dioxide is improved by improving the loading capacity of the adsorption material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a method for preparing a carbon dioxide adsorption catalyst by utilizing fly ash and lithium battery black powder, and a fly ash and coal ash pretreatment and preparation process and equipment. Background Art

[0002] The existing catalyst production method is to mix and stir the substrate and active material and then dry and calcine. The processing method is single, making it difficult to evenly load the active material on the surface of the substrate.

[0003] Fly ash is a kind of hazardous waste. After low-temperature thermal decomposition to remove dioxins and water washing to remove soluble inorganic salts, it becomes general solid waste. Currently, fly ash comes from the product of waste incineration power generation. It does not have many uses and is generally backfilled. Common fly ash resource utilization methods such as brick making, paving, and aggregates are all low-value methods. Since the fly ash composition is similar to the commonly used catalyst materials such as molecular sieves and zeolites, exploring fly ash preparation catalysts has also become an effective way to utilize fly ash resources and realize high-value utilization of fly ash.

[0004] The black powder of waste lithium batteries is a mixture formed after the pyrolysis of lithium battery positive electrode materials, usually containing lithium, cobalt, nickel, manganese and other valuable metal elements. The effective recovery and utilization of the black powder produced by the pyrolysis of waste lithium batteries has great economic and environmental significance. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process for preparing a carbon dioxide adsorption catalyst by utilizing fly ash and lithium battery black powder, so that the fly ash and waste lithium battery black powder can be effectively utilized.

[0006] In order to achieve the above object, the present invention provides a process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder, comprising: S1, after mixing fly ash particles with lithium battery black powder, soaking them in lithium hydroxide solution, drying them and then calcining them, and then cooling and grinding them in sequence to form a catalyst substrate, and finally pneumatically conveying the obtained catalyst substrate to a reactor; wherein the mass ratio of the fly ash particles to the lithium battery black powder is (1.5-3):1; the concentration of the lithium hydroxide solution is 1-10%; S2, pneumatically conveying an ethanol solution of fluorosilicic acid or an ethanol solution of hydrofluoric acid to the reactor at (450-500)°C, wherein the mass fraction of fluorosilicic acid or hydrofluoric acid in the solution is 0.1%-1%; then pneumatically conveying n-hexane to the reactor at (150-200)°C, wherein the volume ratio of the ethanol solution of fluorosilicic acid or the ethanol solution of hydrofluoric acid to n-hexane is 1:(0.3-3); allowing the ethanol solution of fluorosilicic acid or the ethanol solution of hydrofluoric acid and n-hexane to fully contact with fly ash particles; S3, introducing nitrogen gas at 400-500° C. to purge the reactor to remove ethanol, water vapor, and n-hexane in the reactor, and then introducing water vapor to purge to remove residual fluorosilicic acid, fluoride ions, alkanes, and alcohols; and finally introducing nitrogen gas at 400-500° C. to replace the water vapor; S4, after pneumatically conveying diesel to the reactor, introducing 600-800° C. nitrogen to purge the fly ash particles in the reactor, so that the diesel is rapidly carbonized and loaded on the surface of the fly ash particles, wherein the mass ratio of the diesel to the mass of the fly ash particles obtained in S3 is 1:(10-30); S5, prepare a n-hexane solution of hydrated silica gel, the mass fraction of hydrated silica gel is 5%~20%, and transport the solution to the reactor to mix with the catalyst substrate, the mass ratio of the solution to the catalyst substrate obtained in S4 is 5~20:1, then, transport the alcohol solution of silane coupling agent to the reactor, the mass ratio of the silane coupling agent to the n-hexane solution of hydrated silica gel is 1:(3~10); after sufficient mixing, replace and exhaust the n-hexane, and then dry and cool, and the catalyst preparation is completed.

[0007] Preferably, in step S1, the drying process is carried out in an environment of 90% to 98% by volume nitrogen and 2% to 10% by volume hydrogen; and the calcining process is carried out in a nitrogen environment.

[0008] Preferably, in step S1, nitrogen is used to pneumatically transport the fly ash particles to the reactor.

[0009] Preferably, in step S2, nitrogen is used to transport the ethanol solution of fluorosilicic acid to the reactor.

[0010] Preferably, in step S2, the ethanol solution of fluosilicic acid further comprises a high temperature resistant water-soluble surfactant in an amount of 1.5-3.5% by mass of the solution.

[0011] Preferably, in step S2, water vapor is used to transport the n-hexane to the reactor.

[0012] Preferably, in step S2, the n-hexane is further mixed with a high temperature resistant oil-soluble surfactant accounting for 1.5% to 3.5% by mass of the n-hexane.

[0013] Preferably, in step S5, the hydrated silica gel n-hexane solution further comprises a rapid penetrant T accounting for 0.5% to 1.5% by mass of the solution, and a rapid dispersant OT-75 accounting for 0.5% to 1.5% by mass of the solution.

[0014] Preferably, the specific surface area of ​​the fly ash particles in step S1 is 30-80m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S2 is 280-350m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S3 is 230-300m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S4 is 210-240m 2 / g; The specific surface area of ​​fly ash particles can be controlled by controlling the reaction time.

[0015] Preferably, the alcohol in the alcohol solution in step S5 is at least one of methanol and ethanol.

[0016] The present invention also discloses a preparation system used in the above preparation process, comprising: A first material tank, used for storing the ethanol solution of fluosilicic acid in step S2, and pneumatically conveying it to the reactor through a first stream; A second material tank, used for storing the n-hexane in step S2, and pneumatically conveying it to the reactor through a second stream; A third material tank, used for storing the diesel in step S4, and pneumatically transporting the diesel to the reactor via a third stream; a fourth material tank, used for storing the fly ash particles in step S1, and pneumatically conveying them to the reactor via a fourth stream; The reactor further comprises a material outlet at the bottom and a tail gas outlet at the top, and the tail gas outlet is connected to the fifth stream.

[0017] The beneficial effects of the present invention include: providing a preparation process and system for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder, so that fly ash can be effectively utilized. And through a variety of process means, gas phase or gas phase + vapor phase corrosion, gas phase adsorption deposition, gas phase pressurized deposition, gas-solid catalytic reaction, vapor phase catalytic reaction, coking reaction, carbonization reaction, catalytic reaction, water vapor atmosphere activation, nitrogen atmosphere activation, hydrogen atmosphere activation, alkaline steam activation, acidic steam activation and other methods, the substrate surface area and porosity of fly ash and lithium battery black powder are increased, the degree of adhesion of active materials is increased, and the catalyst space velocity is increased; it is avoided that the active material blocks the gap of the catalyst substrate or adheres unevenly during the preparation process, thereby reducing the surface area of ​​the product catalyst and reducing the catalyst's adsorption capacity for carbon dioxide; and the process equipment can achieve continuous operation and industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a process flow chart of preparing a carbon dioxide adsorption catalyst by washing desalinated fly ash with water according to the present invention; Figure 2 is a schematic diagram of the reactor; Figure 3 Schematic diagram of the material tank.

[0019] Reference numerals: 10-first material tank; 101-first material tank outlet valve; 11-first stream; 111-first stream control valve; 20-second material tank; 21-second stream; 211-second stream control valve; 30-third material tank; 301-third material tank outlet valve; 31-third stream; 311-third stream control valve; 40-fourth material tank; 401-fourth material tank outlet valve; 41-fourth stream; 411-fourth stream control valve; 51-fifth stream; 511-pressure control valve; 52-sixth stream; 521-sixth stream control valve; 60-reactor; 601-first inlet; 602-second inlet; 603-third inlet; 604-fourth inlet; 605-exhaust outlet; 606-material outlet; 607-third sprayer; 608-dust removal grid; 609-first sprayer; 610-catalyst sampling port; 611-first material level meter port; 612-pressure change port; 613-temperature change port; 614-second material level meter port; 615-third material level meter port; 616-second sprayer; 901-second check valve; 902-second control valve; 903-inlet; 904-first control valve; 905-first check valve; 906-first venturi ejector; 907-second venturi ejector; 908-outlet; 909-manhole; 910-material tank body; 911-feed port; 912-first pipeline; 913-second pipeline; 914-third pipeline. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the description of the present invention, it should be noted that the terms "upper", "lower", "front", "back", "inside", "outside", "top", "bottom", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the present invention.

[0022] In addition, the terms "first", "second", etc. are only used for descriptive purposes, and do not refer to the limitation of time sequence, quantity, or importance. They cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features, but are only for distinguishing one technical feature from another technical feature in the technical solution. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically specified. Similarly, the qualifiers similar to "one" appearing in this article do not refer to the limitation of quantity, but describe technical features that have not appeared in the previous text. Similarly, unless it is a noun modified by a specific quantitative quantifier, it should be regarded as including both singular and plural forms in this article, and the technical solution can include both singular and plural technical features. Similarly, modifiers similar to "approximately" and "approximately" appearing before the numerals in this article usually include the number itself, and their specific meanings should be understood in conjunction with the context.

[0023] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0024] Unless clearly indicated to the contrary, each aspect or embodiment defined herein may be combined with any other aspect or embodiments. In particular, any feature indicated as preferred or advantageous may be combined with any other feature indicated as preferred or advantageous.

[0025] The present invention discloses a process and system for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder. The system includes a reactor 60 and a plurality of material tanks, including at least a first material tank 10, a second material tank 20, a third material tank 30, and a fourth material tank 40. Correspondingly, the material in the first material tank 10 is pneumatically conveyed to the reactor 60 through a first stream 11, the material in the second material tank 20 is pneumatically conveyed to the reactor 60 through a second stream 21, the material in the third material tank 30 is pneumatically conveyed to the reactor 60 through a third stream 31, and the material in the fourth material tank 40 is pneumatically conveyed to the reactor 60 through a fourth stream 41. Pneumatic conveying can make it more convenient for operators to pass materials into the reactor, and the operation can be completed at a lower height. Among them, the gas used to input the materials from the above-mentioned material tanks into the reactor is selected from inert gas to avoid oxidation of the materials at high temperatures.

[0026] The material tank includes a first pipeline 912 and a second pipeline 913; the first pipeline 912 is connected to the lower part of the tank body, and a first venturi injector 906 is provided at a position below the tank body that is connected to the first pipeline 912; the second pipeline 913 is connected to the upper part of the material tank body 910 and an inlet 903 of the first pipeline 912. In some embodiments, the first pipeline 912 and the second pipeline 913 are both provided with control valves, which are respectively denoted as the first control valve 904 and the second control valve 902; in specific use, the first control valve 904 and the second control valve 902 are opened in sequence, so that the gas passes through the first pipeline 912 and the second pipeline 913, so that the material tank body 910 has sufficient pressure, so that the material in the material tank body 910 enters the first pipeline. In some embodiments, the material tank further includes a third pipeline 914, which is connected to the top of the tank body and the outlet 908 of the first pipeline 912, and is used to prevent excessive gas from entering the second pipeline 913, resulting in excessive pressure in the material tank body 910, which may cause safety hazards. A second venturi injector 907 is provided at the connection between the third pipeline 914 and the first pipeline 912. The first venturi injector 906 and the second venturi injector 907 are both used to inject materials into the outlet 908 of the first pipeline 912.

[0027] The reactor is a cylindrical structure that is wide at the top and narrow at the bottom, so that the fly ash particles can fall after being purged. The positions where the first stream 11, the second stream 21, the third stream 31, and the fourth stream 41 enter the reactor 60 are respectively recorded as the first inlet 601, the second inlet 602, the third inlet 603, and the fourth inlet 604. The order of these positions from bottom to top is the first inlet 601, the second inlet 602, the fourth inlet 604, and the third inlet 603. It also includes a material outlet 606 at the bottom and an exhaust gas outlet 605 at the top. In some embodiments, the material outlet 606 is connected to the sixth stream 52. In some embodiments, the first inlet 601, the second inlet 602, and the third inlet 603 are all connected to the sprayer in the reactor 60. In some embodiments, a dust removal grille 608 is also provided above the third inlet 603 to prevent the fly ash particles from being blown out from the exhaust gas outlet 605.

[0028] The preparation process of the catalyst comprises: S1, the washed fly ash particles and the recycled lithium battery black powder are mixed and ground at a ratio of (1.5-3):1, and further ground to a particle size of 50-100 nanometers; then the ground particles are soaked in a lithium hydroxide solution with a concentration of 1-10% to form a clay, and the clay is dried and calcined so that the lithium ions adhere to the surface of the catalyst substrate to enhance the catalytic effect; further, the drying temperature is 100-200°C, the drying gas is 90%-98% volume fraction of nitrogen, and 2%-10% volume fraction of hydrogen, and hydrogen is used as a reducing agent to reduce the oxides of the fly ash particles and the lithium battery black powder (except for the oxides of active metals such as CaO and MgO). The calcination temperature is 500-800°C, and the ambient gas during the calcination process is nitrogen. After calcination, it is cooled and ground again to form a catalyst substrate, and then the catalyst substrate is poured into the fourth material tank 40 and then pneumatically transported to the reactor 60.

[0029] In some embodiments, nitrogen is used to pneumatically transport the fly ash particles to the reactor 60 through the fourth stream 41 to prevent the fly ash particles from reacting with water vapor. The amount of nitrogen is adjusted by the fourth stream control valve 411, and the volume flow of the fly ash particles is controlled by the fourth material tank outlet valve 401. The material level is detected by the material level meter of the reactor 60 to determine whether the catalyst fly ash particles in the catalyst preparation reactor 60 have reached the required amount. The fly ash particles are used as catalyst substrates. In some embodiments, the specific surface area of ​​the fly ash particles is 30-80m 2 / g.

[0030] S2, the ethanol solution of fluorosilicic acid is stored in the first material tank 10, and the ethanol solution of fluorosilicic acid is pneumatically conveyed to the reactor 60 at (450~500)℃, in which the mass fraction of fluorosilicic acid is 0.1%~1%, so that the ethanol solution of fluorosilicic acid is fully in contact with the fly ash particles; the fluorosilicic acid is used to dissolve the silicate in the fly ash, thereby achieving the purpose of removing impurities; the ethanol solution can more effectively promote the dispersion of the fluorosilicic acid at high temperature and control the corrosion rate of the fluorosilicic acid on the fly ash; the flow rate of the fluorosilicic acid can be controlled by the outlet valve 101 of the first material tank; in some embodiments, the ethanol solution of fluorosilicic acid is pneumatically conveyed to the reactor 60 through the first stream 11 using nitrogen, and the nitrogen flow rate is controlled by the first stream control valve 111 to prevent the fluorosilicic acid from reacting with water vapor and the ethanol from being oxidized by high-temperature air. The volume ratio of the nitrogen gas to the ethanol solution of fluosilicic acid is (10-15): 1. In some embodiments, the ethanol solution of fluosilicic acid further comprises a high temperature resistant water-soluble surfactant accounting for (1.5-3.5%) of the solution by mass, which can accelerate the dissolution of water-soluble lipids and the cavitation of fly ash by fluosilicic acid, dissolve the cavitation products and bring the cavitation products out through water vapor. The n-hexane is stored in the second material tank 20. While the ethanol solution of fluosilicic acid is passed into the reactor, the n-hexane is pneumatically transported to the reactor 60 at 150-200°C through the second stream 21. Further, the gas in the second stream 21 is water vapor, and the flow rate of the water vapor is controlled by the second stream control valve 211. The water vapor can be used to synergize with the surfactant to separate part of the organic matter. Further, the second material tank also comprises a high temperature resistant oil-soluble surfactant accounting for 1.5-3.5% of the mass fraction of n-hexane, which is used to promote the dissolution of oil-soluble substances in the n-hexane.

[0031] The volume ratio of the ethanol solution of fluorosilicic acid to n-hexane is 1:(0.3-3); the pressure in the reactor 60 is controlled at 0.12-0.18 MPa to accelerate the cavitation process.

[0032] In some embodiments, the fly ash particles formed in this step have a specific surface area of ​​280-350 m 2 / g is a normal condition. The reactor 60 further comprises a catalyst sampling port 610, from which fly ash particles are sampled to measure their specific surface area.

[0033] In some embodiments, the fluorosilicic acid in S2 can be replaced by hydrofluoric acid.

[0034] S3, nitrogen at 400-500°C is introduced into the reactor for purge to remove ethanol, water vapor and n-hexane in the reactor. Further, the nitrogen is introduced from the first stream 11, and water vapor is introduced to purge the fly ash particle bed to remove residual fluorosilicic acid and fluoride ions, and to purge the alcohol of the alkane; further, water vapor is introduced from the second stream 21; finally, nitrogen at 400-500°C is introduced to replace the water vapor.

[0035] S4, store the diesel in the third material tank 30, and pneumatically transport it to the reactor 60 through the third stream 31. In some embodiments, the gas in the third stream 31 is water vapor; the volume ratio of the water vapor to the diesel is (10~30):1. At the same time, nitrogen is introduced into the sixth stream 52 to purge the fly ash particles in the reactor 60 so that the fly ash particles and the diesel can be more fully mixed. Pressurized water vapor can more effectively penetrate the diesel into the deep gaps of the fly ash substrate. The ratio of the steam flow rate after the water vapor and diesel are mixed to the catalyst substrate is (1~3) m 3 / h: 1m 3 In some embodiments, after the lithium hydroxide is mixed with the fly ash particles, the first stream 11 delivers 40-60°C nitrogen to the reactor 60 to dry the fly ash particles. In some embodiments, after the fly ash particles are dried with 40-60°C nitrogen, a sample is taken from the catalyst sampling port 610 to measure its specific surface area. The surface area of ​​the fly ash particles obtained is (210-270) m 2 / g is normal.

[0036] Then, the first stream 11 delivers (500-800)°C nitrogen to the reactor 60 to quickly fluidize, carbonize, and dry the fly ash particles with diesel attached, and the tail gas is discharged from the fifth stream 51 through the tail gas outlet 605. In some embodiments, after carbonization and drying are completed, a sample is taken from the catalyst sampling port 610 to measure its specific surface area, and the surface area of ​​the fly ash particles obtained is (210-240) m 2 / g is normal.

[0037] S5, prepare a n-hexane solution of hydrated silica gel in advance and place it in the third material tank 30, wherein the mass fraction of hydrated silica gel is 5%~15%. Also prepare an alcohol solution of silane coupling agent and place it in the second material tank 20, wherein the mass fraction of silane coupling agent is 5%~15%. In some embodiments, the n-hexane solution of hydrated silica gel also contains a rapid penetrant T with a mass fraction of 0.5%~1.5% and a rapid fraction OT-75 with a mass fraction of 0.5%~1.5% to accelerate the penetration and dispersion of hydrated silica gel into fly ash particles. The third stream 31 transports the n-hexane solution of hydrated silica gel in the third material tank 30 to the reactor 60, and the volume ratio of the solution to the catalyst obtained in S4 is (5~20):1. Then, the second stream 21 transports the alcohol solution of the silane coupling agent in the second material tank 20 to the reactor 60, and the mass ratio of the n-hexane solution of the hydrated silica gel to the alcohol solution of the silane coupling agent is (1-5):1, and then (50-70)°C nitrogen is transported into the reactor 60 through the first stream 11 to dry the fly ash particles until the n-hexane is completely exhausted. After drying, (20-35°C) nitrogen is introduced to slowly cool; at this time, the catalyst preparation is completed. The hydrated silica gel has a strong adsorption capacity, and the silane coupling agent can disperse the hydrated silica gel, so that the hydrated silica gel adheres to the surface of the catalyst substrate.

[0038] The following is a specific description through examples. Example

[0039] S1, porosity 75%, surface area 80-100m 2 / g fly ash is ground to obtain particles with a particle size of 50-100 nanometers for later use; the recycled lithium battery black powder is ground to obtain particles with a particle size of 50-100 nanometers for later use. The fly ash and black powder are evenly mixed and then soaked in a 5% lithium hydroxide solution to make a clay. The prepared clay is first dried in an environment with a nitrogen volume fraction of 95% and a hydrogen volume fraction of 5%, and then calcined at 750°C. The calcined product is ground again to a particle size of 30-80 microns, which is the catalyst substrate.

[0040] 5 m³ of the above-mentioned catalyst substrate is selected; it is placed in the fourth material tank 40 for storage, the amount of nitrogen is adjusted by controlling the fourth stream control valve 411, the catalyst substrate is delivered to the reactor 60 by nitrogen pneumatic conveying, and the material level is detected by the material level meter of the reactor 60 to determine whether the catalyst fly ash substrate of the catalyst preparation reactor 60 has reached the required amount.

[0041] S2, further remove the pollutants such as bio-based grease and petroleum-based grease brought into the catalyst substrate during the production process through gas phase dissolution and extraction, and increase the porosity of the fly ash particles, thereby increasing its surface area. The ethanol solution of 0.5% fluorosilicic acid by mass is stored in the first material tank 10, and the addition amount is controlled by the first material tank outlet valve 101. Nitrogen at 450-500°C is introduced into the first stream 11, and the first stream control valve 111 controls the nitrogen flow rate. 0.5% fluorosilicic acid and 1.5-3.5% ethanol solution of high temperature resistant water-soluble surfactant by mass fraction are mixed in the nitrogen gas phase in an amount of (10:1)~(15:1) and sent to the reactor 60. High nitrogen temperature can accelerate the reaction rate, decompose and gasify the reaction products. If the acid concentration is too high, the reaction will be too violent and produce larger voids. Low concentration of acid will corrode slowly. The surfactant itself does not need to be added too much. Too much will adhere to the surface of the substrate to form a package, but too little will not have a dispersing effect. The pressure at the top of the reactor 60 is adjusted to about 0.15MPa by the pressure control valve 511. At the same time, the second stream 21 is introduced with water vapor at 180°C and 0.15MPa, and the n-hexane containing 1.5-3.5% by mass of the high temperature resistant oil-soluble surfactant stored in the second material tank 20 is mixed and introduced into the reactor 60. The volume flow ratio of water vapor to n-hexane is 5:1; the ratio of the steam phase to the nitrogen phase is 1:(15-17). The volume flow rate of the gas phase and the steam phase is 15 times the volume of the catalyst substrate silica. The water-soluble surfactant can accelerate the dissolution of water-soluble lipids, and at the same time accelerate the cavitation of fly ash by fluorosilicic acid, dissolve the cavitation products and bring out the cavitation products through water vapor; the oil-soluble surfactant can accelerate the dissolution of petroleum-based lipids in n-hexane, and ethanol mainly dissolves and brings out some ester substances. The mixed gas phase continuously contacts the fly ash through the catalyst substrate bed to perform a slow cavitation until the fly ash surface area is detected to reach 280-350m 2 / g meets the requirement. Further, after sampling through the catalyst sampling port, the specific surface area of ​​the catalyst is measured using a specific surface area tester.

[0042] S3, removing impurities from the catalyst substrate; since the catalyst substrate will be adsorbed with various substances mentioned above after the above process, it must be cleaned up, specifically: The first stream 11 is introduced with high-temperature nitrogen to continuously purge the catalyst bed until the water vapor and ethanol-n-hexane are completely removed; at the same time, the water vapor introduced into the second stream 21 is continuously purged into the catalyst bed until the residual fluorosilicic acid or fluoride ions are completely removed, and the alkanes, alcohols, etc. are purged clean, and then the gas in the first stream 11 is replaced with 450°C high-temperature nitrogen to replace the water vapor. The preparation of the activated fly ash substrate is completed.

[0043] S4, diesel is placed in the third material tank 30, and the third stream 31 is water vapor. The water vapor is mixed with the diesel for transportation by adjusting the flow rate through the third material tank outlet valve 301, and the diesel is adjusted by adjusting the flow rate through the third material tank outlet valve 301. The volume ratio of steam to diesel is 10:1. The sixth stream control valve 521 controls the nitrogen pneumatic conveying of the fly ash substrate to circulate to the top of the equipment while spraying the mixed phase of steam and diesel. This process completes the mixing of lithium, diesel and the substrate. The pressurized water vapor can more effectively penetrate the diesel into the deep gaps of the fly ash substrate. The volume ratio of diesel vapor flow to catalyst substrate is 0.1m 3 / h: 1m 3 At the same time, 50°C nitrogen was introduced into the first stream 11 to purge and dry the catalyst substrate, and the catalyst surface area was monitored at any time until the catalyst surface area was between 210-270m 2 The tail gas is discharged from the fifth stream 51 to ensure that the pressure of this process is not less than 0.1 MPa.

[0044] Then, the first stream 11 is introduced with 700°C nitrogen to quickly fluidize, carbonize, and dry the adsorbed diesel catalyst substrate, carbonize the adsorbed diesel, and monitor the catalyst surface area at any time until the catalyst surface area is 210-240m 2 / g. The tail gas is discharged from the fifth stream 51 to ensure that the pressure of this process is not less than 0.1 MPa. The residual water vapor during carbonization plays a role in activating the carbon.

[0045] S5, prepare a 15% by mass fraction n-hexane solution of hydrated silica gel, the solution contains 1% by mass fraction of fast penetrant T and 1% by mass fraction of fast dispersant OT-75, so as to accelerate the penetration and dispersion of silica gel into the catalyst substrate; also prepare an alcohol solution of silane coupling agent and place it in the second material tank 20, wherein the mass fraction of the silane coupling agent is 5% to 15%. A 15% silica gel n-hexane solution is placed in the third material tank 30, and 30°C nitrogen is input into the third stream 31 to mix the solution with the catalyst in a volume ratio of 10:1, so that the catalyst substrate and the 15% hydrated silica gel n-hexane solution are evenly mixed, and then the second stream 21 transports the alcohol solution of the silane coupling agent in the second material tank 20 to the reactor 60, and the mass ratio of the n-hexane solution of the hydrated silica gel to the alcohol solution of the silane coupling agent is 4:1. During the mixing process, 60°C nitrogen is continuously added through the first stream 11 to dry the catalyst until the n-hexane is completely exhausted. After drying, 30°C nitrogen is introduced to slowly cool it; the catalyst preparation is completed.

[0046] Then, a control experiment was conducted on the catalyst obtained in the embodiment. 0.01 m³ of the catalyst obtained in the embodiment was placed in the decarbonization tower. The flue gas entering the decarbonization tower was at normal pressure. 2 The concentration is 88g / m 3 , enter 5m³.

[0047] Comparative Example 1 Silica gel without other treatment was used as the adsorbent, and 0.01m³ was placed in the decarbonization tower. The flue gas condition of the decarbonization tower was the same as that in Example 1.

[0048] The catalyst prepared in Example 1 and Comparative Example 1 were placed in a decarbonization tower for experiments, and the results are as follows.

[0049] Decarburization effect comparison table Test items <![CDATA[CO at the flue gas outlet of the decarbonization tower 2 Concentration / (g / m 3 )]]> Example 7.3 Comparative Example 1 37.1 It can be seen that the catalyst prepared in this example has a good adsorption effect on carbon dioxide in flue gas.

[0050] In summary, the present invention provides a preparation process and system for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder, which has the following advantages over traditional processes: utilizing the carbon dioxide adsorption characteristics of lithium, activated carbon, and silica gel, and increasing the porosity and specific surface area of ​​the adsorbent by treating the catalytic adsorbent; and increasing the adsorption capacity of carbon dioxide by the adsorption catalyst by increasing the loading amount of the adsorbent material.

[0051] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder, characterized in that: Include: S1, after mixing fly ash particles with lithium battery black powder, soaking them in lithium hydroxide solution, drying them and then calcining them, and then cooling and grinding them in sequence to form a catalyst substrate, and finally pneumatically conveying the obtained catalyst substrate to a reactor; wherein the mass ratio of the fly ash particles to the lithium battery black powder is (1.5-3):1; the concentration of the lithium hydroxide solution is 1-10%; S2, pneumatically conveying an ethanol solution of fluorosilicic acid or an ethanol solution of hydrofluoric acid to the reactor at (450-500)°C, wherein the mass fraction of fluorosilicic acid or hydrofluoric acid in the solution is 0.1%-1%; then pneumatically conveying n-hexane to the reactor at (150-200)°C, wherein the volume ratio of the ethanol solution of fluorosilicic acid or the ethanol solution of hydrofluoric acid to n-hexane is 1:(0.3-3); allowing the ethanol solution of fluorosilicic acid or the ethanol solution of hydrofluoric acid and n-hexane to fully contact with fly ash particles; S3, introducing nitrogen gas at 400-500° C. to purge the reactor to remove ethanol, water vapor, and n-hexane in the reactor, and then introducing water vapor to purge to remove residual fluorosilicic acid, fluoride ions, alkanes, and alcohols; and finally introducing nitrogen gas at 400-500° C. to replace the water vapor; S4, after pneumatically conveying diesel to the reactor, introducing 600-800° C. nitrogen to purge the fly ash particles in the reactor, so that the diesel is rapidly carbonized and loaded on the surface of the fly ash particles, wherein the mass ratio of the diesel to the mass of the fly ash particles obtained in S3 is 1:(10-30); S5, prepare a n-hexane solution of hydrated silica gel, the mass fraction of hydrated silica gel is 5%~20%, and transport the solution to the reactor to mix with the catalyst substrate, the mass ratio of the solution to the catalyst substrate obtained in S4 is 5~20:1, then, transport the alcohol solution of silane coupling agent to the reactor, the mass ratio of the silane coupling agent to the n-hexane solution of hydrated silica gel is 1:(3~10); after sufficient mixing, replace and exhaust the n-hexane, and then dry and cool, and the catalyst preparation is completed.

2. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S1, the drying process is carried out in an environment of 90% to 98% by volume nitrogen and 2% to 10% by volume hydrogen; and the calcining process is carried out in a nitrogen environment.

3. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S1, the fly ash particles are pneumatically transported to the reactor using nitrogen.

4. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S2, nitrogen is used to transport the ethanol solution of fluorosilicic acid to the reactor.

5. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S2, the ethanol solution of fluorosilicic acid further comprises a high temperature resistant water-soluble surfactant in an amount of 1.5-3.5% by mass of the solution.

6. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S2, the n-hexane is transported to the reactor using water vapor.

7. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S2, the n-hexane is further mixed with a high temperature resistant oil-soluble surfactant accounting for 1.5% to 3.5% by mass of the n-hexane.

8. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: In step S5, the hydrated silica gel n-hexane solution further comprises a rapid penetrant T accounting for 0.5% to 1.5% by mass of the solution, and a rapid dispersant OT-75 accounting for 0.5% to 1.5% by mass of the solution.

9. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: The specific surface area of ​​the fly ash particles in step S1 is 30-80m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S2 is 280-350m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S3 is 230-300m 2 / g; the specific surface area of ​​the fly ash particles obtained in step S4 is 210-240m 2 / g; The specific surface area of ​​fly ash particles can be controlled by controlling the reaction time.

10. The process for preparing a carbon dioxide adsorption catalyst using fly ash and lithium battery black powder as claimed in claim 1, characterized in that: The alcohol in the alcohol solution in step S5 is selected from at least one of methanol and ethanol.

11. A preparation system for use in the process according to any one of claims 1 to 10, characterized in that: Include: A first material tank, used for storing the ethanol solution of fluosilicic acid in step S2, and pneumatically conveying it to the reactor through a first stream; A second material tank, used for storing the n-hexane in step S2, and pneumatically conveying it to the reactor through a second stream; A third material tank, used for storing the diesel in step S4, and pneumatically transporting the diesel to the reactor via a third stream; a fourth material tank, used for storing the fly ash particles in step S1, and pneumatically conveying them to the reactor via a fourth stream; The reactor further comprises a material outlet at the bottom and a tail gas outlet at the top, and the tail gas outlet is connected to the fifth stream.